Pengaruh Peran Guru Pendidikan Agama Islam (PAI) terhadap Peningkatan Literasi Baca Tulis Al-Qur’an (BTQ) pada Siswa Sekolah Dasar (SD) Kelas VI di Kecamatan Balongan Kabupaten Indramayu - Nurul Inayah; Siti Mulkiyah; Fitriah Fitriah; Muhammad Aulia Taufiqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the extent of the influence of Islamic Education (PAI) teachers' roles in improving Qur’anic Literacy (BTQ) among sixth-grade elementary school students in Balongan District, Indramayu Regency. The research employs a quantitative approach using a correlational method to examine the relationship between the two variables in a more measurable way. A total of 200 students were selected as the research sample using a probability sampling technique to ensure fair representation of the population. Data collection was carried out through two main instruments: a questionnaire to measure the perceived role of PAI teachers and a test to assess students’ BTQ skills. The collected data were analyzed with the help of SPSS version 26 using the Pearson Product Moment correlation technique. The analysis results showed a correlation value of 0.535 with a significance level of 0.05, indicating a strong and significant relationship between the role of PAI teachers and students’ BTQ literacy. Therefore, it can be concluded that PAI teachers have a positive influence in enhancing students’ ability to read and write the Qur’an.